The Mental Health of Migrants in Northern Ireland - Patel, Kishan; Kouvonen, Anne; Bosqui, Tania; Vannanen, Ari; O'Reilly, Dermot (International Journal of Population Data Science, 2018)
Background Research has shown that the health of migrants can vary dramatically from the health of the settled population of their countries. Whilst migrant health has been studied in other areas of the UK, it is especially important to research the mental health of migrants in Northern Ireland specifically, due to the country’s unique mental health situation. Objectives This study aims to assess the mental health of migrants in Northern Ireland as compared to the settled majority population, both by way of reported poor mental health, and psychotropic prescription medication uptake. Methods This study uses a cohort of 1,019,769 people in Northern Ireland, taken from the 2011 Census of Northern Ireland and the BSO Enhanced Prescribing Dataset (2011-2014). The migrant population of Northern Ireland is described in terms of demographic and socioeconomic factors, and logistic regression models are used to analyse the relative risks of reporting poor mental health and uptake of psychotropic medication within the migrant population as compared to the settled population. Findings The results show that migrants were significantly less likely to report poor mental health than the settled population of Northern Ireland, when adjusted for demographic characteristics, socioeconomic factors, and reported poor physical health. Migrants were also significantly less likely to use any form of psychotropic prescription medication than the settled population. Conclusions These findings are in concordance with most research conducted in other countries. The roles of the healthy migrant effect, the salmon bias, stigma, and lack of access to healthcare are discussed as possible reasons for the percieved migrant mental health advantage. However, such a dramatic difference between the health of migrants and the settled population of Northern Ireland may be due, in part, to certain limitations of the datasets used.